UNDERSTANDING THE FEATURES OF MADATYAYA (ALCOHOLISM) - S, *Niranjan; Swayamprava, Swapna (International Journal of Ayurveda and Pharma Research, 2017)
Alcoholism is one of the serious social problems which is rapidly increasing in every year. The fastest growth is being observed in the developing countries of Asia more particularly in India. Drinking of alcohol makes the life of a man very miserable. Alcohol not only degrades the health of the person but also affects his family and society. In Ayurveda, the varieties of illnesses caused by the improper use of alcohol are grouped under one heading Madatyaya. In this contemporary era every disease is being understood by comparing it with modern parlance. Here is a small effort to understand the features of Madatyaya in terms of modern perspective. The disease Madatyaya is classified into Vatika, Paittika, Kaphaja, Sannipataja (based on Doshic predominance), Panatyaya, Paramada, Panajeerna, Panavibhrama, Dhwamsaka and Vikshaya. The different signs and symptoms mentioned in these types, complications of Madatyaya as well as the features of bad prognosis of Madatyaya can be understood based on available modern descriptions. By understanding the features of Madatyaya we can say that Madatyaya is not just an alcohol intoxication, dependence or withdrawal state, but it is the condition where multiple systemic dysfunctions are involved from immediate and acute manifestations to chronic and severe manifestations. Neurological, gastro-hepatic and cardio-pulmonary manifestations are the commonest features seen in the patients of Madatyaya which is also similar to the descriptions of alcoholism. Thus we can say that the word alcoholism which is used in broad sense can be said as equivalent to the word Madatyaya.